NAVIGATING THE DIGITAL TALENT ODYSSEY: AN IN-DEPTH EXPLORATION OFRECRUITMENT STRATEGIES, SKILLSET DYNAMICS, AND PERFORMANCE OUTCOMES IN INDONESIAN DIGITAL MARKETING - Kosasih Kosasih; Almira Luthfiyanti Kosasih, Imas Siti Masitoh, Grace Angela Philips, Ida Ayu Triana (CV. Adiba Aisha Amira, 2024)
In the ever-evolving landscape of Indonesian digital marketing, the journey to secure and nurture digital talent is akin to an odyssey. This study delves into the intricate web of recruitment strategies, skillset dynamics, and performance outcomes in this dynamic sector. Recruitment strategies in Indonesian digital marketing are multifaceted, encompassing social media sourcing, headhunting, competency-based assessments, and cultural alignment. These strategies are pivotal in identifying individuals who can thrive in the fast-paced, ever-changing industry. Skillset dynamics are the heart of digital marketing success. Professionals must continuously adapt to evolving skill set requirements, including SEO expertise, data analytics proficiency, and creative marketing skills. Staying updated with industry trends and embracing technology, particularly AI and automation, are essential. Performance outcomes, including ROI, conversion rates, and brand engagement, serve as success metrics. Talent retention is equally critical, involving onboarding, skill development, diversity and inclusion, data privacy, and building talent pools. The interplay between recruitment strategies, skill development, and performance outcomes defines success in Indonesian digital marketing. HR professionals and organizations must navigate this complex terrain, embracing multifaceted recruitment, cultural alignment, soft skill assessment, agility, continuous learning, and technology adoption. Together, these elements forge a path to digital marketing success.